(untitled) (Medico Legal Update, 2021)
This study aims to analyze the rationality and application of strict liability for environmental offenses in the Environmental Protection and Management Act of Indonesia. The strict liability set out in this law expressly applies only to civil cases and covers the possibility that it may be used in criminal matters. Normative legal research complemented by a statutory and conceptual approach was used. The results showed that it generally applies to regulatory offenses aimed at protecting the public interest. This doctrine is necessary to improve the long-term and prevents harm to people or the environment. The absence of mental element proof should be limited to offenses that are characterized by the administrative dependence of criminal law, which is reflected in the abstract and concrete endangerment models. Generally, prohibited behavior related to waste/emissions disposed into the environment without approval causes damage. The offense is formulated as formal offense by eliminating the element of the perpetrator’s culpability, and it is therefore not necessary to prove it.